. A contribuição do Serviço Social na concepção de educação permanente e no processo de profissionalização dos/as trabalhadores/as do Sistema Único de Assistência Social (SUAS) - Araujo, Uilson José Gonçalves (2023)
This dissertation is the result of a research that places the Permanent Education of the Unified Social Assistance System (SUAS) as an object of study. Every day, SUAS workers face new challenges in the operationalization and consolidation of public social assistance policy in Brazil, requiring investment in permanent education policy. The expansion of this complex and recent System requires the reconfiguration, qualification and improvement of management capacity and professional practice. The NOB-SUAS (2005/2012), NOB-RH/SUAS (2006) and PNEP/SUAS (2013) impose processes of establishment and implementation of the permanent education policy for SUAS workers in the benefits, services, programs and projects at all levels of social protection and social control. The study problematizes the following question: What is the contribution of Social Services in the conception of permanent education and in the process of worker’s professionalization in the Unified Social Assistance System - SUAS - in Brazil? The general objective was to analyze this issue based on the following specific objectives: historically contextualize the demands for Permanent Education in Social Assistance Conferences in Brazil and SUAS normative documents; analyze the relationship between continuing education and work in social assistance policy; analyze the process of constructing the concept of permanent education in SUAS; understand the movement and struggle of social workers for permanent education at SUAS. Based on the theoretical-methodological reference of historical-dialectical materialism, we sought to articulate different dimensions in the unveiling of reality with bibliographical research, documentary research and field research. The field research consisted of 7 (seven) semi-structured interviews with social workers who participated in the Commission that proposed the text of NOB-RH/SUAS, with the criteria being professionals who continue to work with active registration in CRESS. The exhibition is organized into three chapters that dialogue from the first chapter with the reports of the research subjects. In the end, as well as a starting point, the leading role and critical influence of Social Work in the conception of permanent education at SUAS is considered and reaffirmed.